2005
DOI: 10.1093/qjmed/hci052
|View full text |Cite
|
Sign up to set email alerts
|

Usage of troponin in the real world: a lesson for the introduction of biochemical assays

Abstract: The introduction of troponin assays into widespread use requires careful assessment. cTnI requests and subsequent patient management remain below expected standards. Ideally, the laboratory should provide an accurate result within a reasonable time frame, while physicians need to request cTnI at a suitable time-point and use the result appropriately. Lessons from the introduction of cTnI measurement may be useful for the introduction of future new tests in other areas of cardiology and medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…14,15 On the whole, the results of the current study confirmed those of similar studies conducted in other parts of the world. 16,17 18,19 Although these measures may help reduce patient wait times, it often results in unnecessary tests being ordered.…”
Section: Discussionsupporting
confidence: 89%
“…14,15 On the whole, the results of the current study confirmed those of similar studies conducted in other parts of the world. 16,17 18,19 Although these measures may help reduce patient wait times, it often results in unnecessary tests being ordered.…”
Section: Discussionsupporting
confidence: 89%
“…Modern hs-Tn assays provide an opportunity to improve ACS diagnosis and patient outcomes, but, like any clinical tool, these need to be applied appropriately for optimum benefits. Data showed that the introduction of these tests at a UK hospital was suboptimal, with problems including inappropriate requests, 55 incomplete information in the laboratory request 56 and long turnaround times for results. 56 The Asia Pacific consensus group recommends regular education of personnel on the appropriate use of troponin tests in clinical practice, including: The analytical characteristics of the test used at that hospital/medical centre The need for serial testing in all patients The interpretation of the results in relation to the 99th percentile for that particular assay, including gender differences, the units used, changes over time versus stable levels The integration of hs-Tn results into the diagnostic algorithm, alongside other information from the patient's history, clinical signs, ECG and imaging results Caution in interpretation in presence of comorbidities.…”
Section: Resultsmentioning
confidence: 99%
“…Exemplifying the need to learn from past mistakes, an early audit following introduction of troponin testing in a UK hospital, for example, demonstrated no advantage to patients or the NHS of the test in selecting patients for further cardiac investigation and/or reducing length of stay 34 . Reasons identified for this most unexpected conclusion were simple.…”
Section: Future Prospectsmentioning
confidence: 99%